2005
DOI: 10.2337/diabetes.54.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Diabetes and Resistance to Xenograft Transplantation Tolerance in NOD Mice

Abstract: Costimulation blockade induces prolonged rat islet and skin xenograft survival in C57BL/6 mice. Nonobese diabetic (NOD) mice, which are used to model human autoimmune diabetes, are resistant to costimulation blockade-induced allograft tolerance. We tested the hypothesis that NOD mice would also be resistant to costimulation blockade-induced rat xenograft tolerance. We report that rat islet xenograft survival is short in spontaneously diabetic NOD mice treated with a tolerizing regimen of donor-specific transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Moreover, we tried a number of induction protocols to generate chimerism in NOD mice (our unpublished observations), but with the exception of the protocol reported in this study, we were unable to achieve stable mixed chimerism, thus preventing us from assessing split tolerance. This is clearly consistent with the known tolerance resistance of NOD mice (21)(22)(23) and indicates that greater requirements must be met for chimerism induction in the NOD model. However, it does not appear that the level of chimerism by itself explains the rejection of donor islets in NOD but not B6 chimeras, as even a very low-level chimerism (1-3%) was sufficient to prevent rejection of fully mismatched donor islets in B6 mice (Figs.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Moreover, we tried a number of induction protocols to generate chimerism in NOD mice (our unpublished observations), but with the exception of the protocol reported in this study, we were unable to achieve stable mixed chimerism, thus preventing us from assessing split tolerance. This is clearly consistent with the known tolerance resistance of NOD mice (21)(22)(23) and indicates that greater requirements must be met for chimerism induction in the NOD model. However, it does not appear that the level of chimerism by itself explains the rejection of donor islets in NOD but not B6 chimeras, as even a very low-level chimerism (1-3%) was sufficient to prevent rejection of fully mismatched donor islets in B6 mice (Figs.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, our NOD recipients could be more resistant to chimerism-induced tolerance of islets due to islet autoimmunity (31) and their known resistance to tolerance induction strategies (21)(22)(23). However, although islet-specific autoimmunity could lead to donor islet rejection by chimeras, as suggested in a previous study (32), the lack of syngeneic islet rejection in our study indicated that autoimmunity could not explain the split tolerance.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…These observations are consistent with the development of T1D in NOD mice associated with reduced IL-2 levels [18,19], and furthermore, Idd3 alleles are known to affect the development of a number of other autoimmune diseases, including autoimmune ovarian dysgenesis [31], experimental autoimmune encephalomyelitis [32], and Sjögren's syndrome-associated manifestations [33,34]. In addition, experiments utilizing Idd3 congenic mouse strains demonstrated that mice with Idd3 susceptibility alleles have reduced sensitivity to tolerance induction to allogeneic [35] and xenogeneic [36] islet grafts. Similarly, protective alleles at Idd3 and Idd5 facilitated islet-antigen specific tolerance as compared with NOD mice; the proliferation of autoreactive CD8 + T cells was greatly reduced in the pancreatic lymph nodes (PLNs) upon activation by cross-presented islet antigens and migration to the islets appeared to be eliminated [37].…”
supporting
confidence: 75%